High-resolution degenerate four-wave-mixing spectroscopy of OH in a flame with a novel single-mode tunable laser - Bultitude, K; Stevens, R; Ewart, P (2004)
The first application of a novel single-mode tunable laser system to nonlinear spectroscopy is reported. The device uses a modeless dye laser, pumped by a single longitudinal mode (SLM) Q-switched Nd:YAG laser, as a narrow-bandwidth amplifier of the output of a SLM diode laser. The system provides pulses of 5-ns duration, 30-mJ energy and 165-MHz spectral line width tunable in the range 632-639 run at 10-Hz repetition rate. The frequency-doubled output of the laser is used to record spectral line shapes of degenerate four wave mixing (DFWM) signals from the P1(15) line of the A2σ-X2π (0, 0) band of OH in a methane/ oxygen flame. Pressure broadening of the DFWM line shape is studied for the first time in a low-pressure flame and a pressure-broadening rate of 1.31 ± 0.09 × 10-4 cm-1/Torr is derived from the data. Powerbroadening effects are measured and compared with predictions of the standard perturbative model and of an analytical solution derived from a non-perturbative treatment of DFWM with arbitrary pump and probe intensities.